PENGARUH FASILITAS KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS PERPUSTAKAAN DAERAH (DPAD) KOTA BIMA - Firman, Firman; Wulandari, Wulandari; Jaenab, Jaenab (Journal MISSY (Management and Business Strategy), 2023)
The purpose of this research is to find out whether there is a significant effect between work facilities on employee performance, to find out whether there is a significant effect between work competence on employee performance and to find out whether there is a simultaneous effect between work facilities and competence on employee performance at the Regional Library Service (DPAD). ) City of Bima. In this study, the population was 50 respondents using purposive sampling technique. The type of data used in this study was qualitative data. The data collection technique used was literature study, documentation and questionnaires. The research location was at the Regional Library Service (DPAD) ) Kota Bima, the data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression test and t test. The results showed that there was no significant influence between Work Facilities on Employee Performance at the Regional Library Service (DPAD) Kota Bima, There was a significant influence between Work competence on Employee Performance at the Regional Library Service (DPAD) Bima City and there was a simultaneous influence between Work Facilities and Competencies on Employee Performance at the Regional Library Service (DPAD) Kota Bima.